Community of self-organisation: supply chain perspective of Finnish electronic music. (15th October 2008) - Hardaker, Glenn; Graham, Gary
This article analyses the overlapping of consumption and production on the supply chain for electronic dance music sector in Finland. Although the music establishment have seen their control and production of music consolidate over the last 50 years as a high-value, capital growth process, the structural formation of the music industry in Finland is presented as one being fractured to the extent that producer and consumer identities have been blurred. The creation and consumption of electronic music is shown to be led by the decentralised nature of the supply chain network. Our findings from the Finland study challenge the conventional distinction between consumer and producer of music, with the record label typically acting as a mediator between them, in the supply chain. The supply chain concept (in Finland) is experiencing a fundamental paradigm shift with respect to the music industry, that is being evidenced by the following research findings: the methods of production and supply are highly integrated through the creation of peer-to-peer communities; the electronic music industry, is seeing the overlapping of traditional cultural consumption and production; and the emergent self-organisation.